Cohort profile: healthy and active ageing in Myanmar (JAGES in Myanmar 2018): a prospective population-based cohort study of the long-term care risks and health status of older adults in Myanmar. Issue 10 (31st October 2020) - Win, Hla Hla; Nyunt, Than Win; Lwin, Kay Thi; Zin, Poe Ei; Nozaki, Ikuma; Bo, Thae Zarchi; Sasaki, Yuri; Takagi, Daisuke; Nagamine, Yuiko; Shobugawa, Yugo
Abstract : Purpose: Myanmar is rapidly ageing. It is important to understand the current condition of older adults in the country. To obtain such information, we conducted home-visit surveys to collect data for evaluating social determinants of health on older adults in Yangon (representative of an urban) and Bago (representative of a rural) regions of Myanmar. Participants: Overall, 1200 individuals aged 60 years or older and who were not bedridden or had severe dementia (defined as an Abbreviated Mental Test score ≤6) were recruited from Yangon and Bago in 2018. A population-proportionate random-sampling method was used for recruitment. Findings to date: Overall, 600 individuals from Yangon (222 men; 378 women) and 600 from Bago (261 men; 339 women) were surveyed. The average age of Yangon-based men and women was 69.4±7.6 and 69.4±7.3 years; in Bago, this was 69.2±7.1 and 70.6±7.5 years, respectively. Compared to their Yangon-based counterparts, Bago-based respondents showed significantly lower socioeconomic status and more commonly reported poor self-rated health (Bago-based men: 32.2%, women: 42.5%; Yangon: 10.8% and 24.1%, respectively). Meanwhile, some Yangon-based respondents rarely met friends (men: 17.1%, women: 27.8%), and Yangon-based respondents scored higher for instrumental activities of daily living and body mass index when compared to their Bago-based counterparts. For both regions, women showed higher physical-function decline (Yangon-based women: 40.7%, men: 17.1%; Bago: 46.3% and 23.8%, respectively) and cognitive-function decline (Yangon: 34.1% and 10.4%, respectively; Bago: 53.4% and 22.2%, respectively). Being homebound was more common in urban areas (urban-based men: 11.3%, rural-based men: 2.3%; urban-based women: 13.0%, rural-based women: 4.7%, respectively). Future plans: A follow-up survey is scheduled for 2021. This will afford longitudinal data collection concerning mortality, becoming bedridden, and developing dementia and long-term care-related diseases. This will allow us to calculate long-term care risks for older adults in Myanmar.